AB0132 A NOVEL TARGET FOR TREATMENT OF INFLAMMATORY JOINT DISEASES. (June 2019) - Lindquist, Susanne; Alenius, Gerd-Marie; Berntson, Lillemor; Dahlqvist, Solbritt Rantapää; Lundberg, Lennart; Wang, Yuhang; Hernell, Olle
Abstract : Background: The bile salt-stimulated lipase (BSSL) is a hitherto unrecognized player in inflammation. Animals devoid of BSSL (knockout mice) are protected from developing collagen induced arthritis (CIA) and collagen antibody induced arthritis (CAIA), and antibodies directed towards BSSL has been proven to prevent or mitigate arthritis in mouse and rat arthritis models 1 . In humans, BSSL is present in blood 2 and accumulate at sites of inflammation. Patients with acute pancreatitis have significantly increased plasma BSSL levels compared to healthy controls. Whether BSSL in blood originates from pancreas, inflammatory cells, or both remains to be elucidated. Objectives: To determine BSSL concentration in blood samples from patients with inflammatory joint disorders and to evaluate possible relationships between circulating BSSL levels and disease-activity variables. Methods: BSSL concentrations in plasma or serum were determined in patients with rheumatoid arthritis (RA), psoriasis arthritis (PsA), and juvenile idiopathic arthritis (JIA) by a sandwich enzyme-linked immunosorbent assay (ELISA). Correlations between BSSL concentrations and disease activity score, erythrocyte sedimentation rate (ESR), blood levels of C-reactive protein (CRP), S100A8/9, leukocyte- and neutrophil counts, proinflammatory cytokines and chemokines were analyzed using Spearman rank-order correlation. Results: Significant correlations between BSSL concentration in plasma and disease activity score (DAS28, rS =0.31, p=0.007), ESR (rS =0.58, p<0.000), CRP (rS =0.42, p=0.012), leukocytes (rS =0.66, p<0.000), and neutrophils (rS =0.71, p<0.000) were found in RA. The BSSL plasma concentration decreased with duration of treatment with the TNFα inhibitor infliximab, in parallel with decreasing DAS28 score. BSSL concentration was significantly higher in sera from PsA patients with both oligo- and polyarthritis compared with healthy controls. Moreover, BSSL concentration in serum correlated significantly with S100A8/A9 and CRP concentrations (rS =0.54, p<0.001 and rS =0.49, p<0.001, respectively). No correlation between levels of BSSL and cytokines or chemokines were found in RA or PsA plasma or serum, respectively. In JIA, levels of BSSL in serum correlated significantly with JIA disease activity score (JADAS27) (rS =0.26, p=0.007), ESR (rS =0.47, p<0.000), and leukocytes (rS =0.32, p<0.000). Conclusion: BSSL concentration in serum and plasma correlated with disease activity in patients with inflammatory joint disorders, i.e. RA, PsA and JIA. These data in humans support the relevance of our previous studies in rodents and therefore also our hypothesis 1 that BSSL is a novel target for treatment of inflammatory diseases. References: [1] Lindquist S, Andersson EL, Lundberg L, Hernell O. Bile salt-stimulated lipase plays an unexpected role in arthritis development in rodents. PLoS One. 2012;7(10):e47006. [2] Blind PJ, Blackberg L, Hernell O, Ljungberg B. Carboxylic ester hydrolase: a serum marker of acute pancreatitis. Pancreas. 1987;2(5):597-603. Acknowledgement: The authors are grateful to Eva-Lotta Andersson for excellent technical assistance. Disclosure of Interests: Susanne Lindquist Shareholder of: Founder and shareholder of Lipum AB, Umeå, Sweden., Grant/research support from: Research support from Lipum AB., Employee of: Employed (50%) by Lipum AB., Gerd-Marie Alenius: None declared, Lillemor Berntson Consultant for: AbbVie, Speakers bureau: AbbVie, Solbritt Rantapää Dahlqvist Consultant for: Member of the advisory board, Lipum AB, Umeå, Sweden., Lennart Lundberg Shareholder of: Founder and shareholder of Lipum AB, Umeå, Sweden., Grant/research support from: Research support from Lipum AB., Employee of: Member of the board, Lipum AB., Yuhang Wang: None declared, Olle Hernell Shareholder of: Founder and shareholder of Lipum AB, Umeå, Sweden., Grant/research support from: Research support from Lipum AB., Employee of: Member of the board, Lipum AB., Speakers bureau: But not within this field of research.